A functional account of Marathi's voice phenomena : passives and causatives in Marathi - Parudeshi, Purashanto, 1965- (Brill, 2016)
A Functional Account of Marathi's Voice Phenomena offers a comprehensive account of the formal and semantic aspects of the two most prominent voice phenomena in Marathi: the passive and the causative. Previous studies offer many partial insights into various aspects of Marathi's passives and causatives. However, a comprehensive description of the formal, semantic, and pragmatic aspects of Marathi's passives and causatives as not been available so far. Attempting to fill this gap, the present monograph offers a description in the functional-typological framework. At the same time it introduces the reader to the rich tradition of grammatical studies in Marathi, which up to now have remained inaccessible to those who are unfamiliar with the language.
Keywords: Marathi language -- Voice.; Marathi language -- Verb.; Marathi language -- Parts of speech.; Marathi language -- Grammar.; Functionalism (Linguistics); Marathe (Langue) -- Voix.; Marathe (Langue) -- Parties du discours.; Marathe (Langue) -- Grammaire.; Fonctionnalisme (Linguistique); FOREIGN LANGUAGE STUDY -- Miscellaneous.; Marathi language -- Grammar; Marathi language -- Verb; Electronic book.